2021
DOI: 10.5296/ijhrs.v11i2.18459
|View full text |Cite
|
Sign up to set email alerts
|

Organisation Justice Towards’ Employees Voluntary Turnover: A Perspective of SMEs in Malaysia

Abstract: Turnover of employees has gained the attention of organisations due to the impact of human resources on organisation performance and competitive advantage. This dilemma leads the management to struggle to find ways and retain employees. To attract, organisations use the "pull factors" to entice employees to perform better in the organisation. This study was conducted to investigate the relationship between the three dimensions of organisational justice: distributive, procedural and interactional justice toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It should be noted that at least two meta-analyses have discovered that procedural justice was negatively related to intentions to quit (e.g., [17,66]). Indeed, when procedural justice [19] is perceived as fair, employees are more engaged and their turnover intentions are lower [20][21][22]. This is shown in our conceptual framework (see Figure 1).…”
Section: Review Of Literature and Formulation Of Research Hypothesesmentioning
confidence: 67%
See 2 more Smart Citations
“…It should be noted that at least two meta-analyses have discovered that procedural justice was negatively related to intentions to quit (e.g., [17,66]). Indeed, when procedural justice [19] is perceived as fair, employees are more engaged and their turnover intentions are lower [20][21][22]. This is shown in our conceptual framework (see Figure 1).…”
Section: Review Of Literature and Formulation Of Research Hypothesesmentioning
confidence: 67%
“…Our first hypothesis "Procedural justice will be negatively related to turnover intention" was confirmed (β = −0.30, p < 0.01) (see Table 3). Indeed, when procedures [19] are perceived as fair, employees are more committed and their turnover intentions become lower [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Cohen-Charash and Spector 2001;Colquitt et al 2001;Gharbi et al 2022) emphasized a negative relationship between procedural justice and turnover intention. Employee engagement in turnover intention was observed to be less when procedural justice was viewed as being fair (Gim and Desa 2014;Chong et al 2021). Hence, we suggest the following: Hypothesis 1 (H1).…”
Section: Procedural Justice and Turnover Intentionmentioning
confidence: 74%
“…If employees perceive unequal procedures, they could respond with a negative attitude, such as exhibiting turnover intention and social loafing behavior. In that sense, previous studies (e.g., Aliedan et al 2022;Alyahya et al 2021;Sobaih et al 2019) argued that an intention to leave is usually associated with negative outcomes, such as low job-performance levels, unethical behavior and social loafing, while pervious research results (e.g., Griffeth et al 2000;Chong et al 2021;Gharbi et al 2022) confirmed that procedural justice is a key driver for employee turnover. Additionally, it was argued that procedural justice is more important than distributive justice in determining employees' evaluations of the parties or the institution that enacted the decision (Brockner and Siegel 1996).…”
Section: Introductionmentioning
confidence: 87%